Correlation between students’ perceived parental expectations and students’ academic engagement: The intermediary effect of academic self-efficacy - Yuting Wang; Fatimah B. Tambi (Journal of Pedagogical Research, 2024)
This article aims at exploring the correlation of student’ perceived parental expectations, academic self-efficacy and academic engagement based on the expectancy value theory. Specifically, this study innovatively integrated the parental expectations, academic self-efficacy and academic engagement from students’ perspectives into one model and explored the relationships between them. This study adopted quantitative questionnaire survey, including three instruments. This study adopted the Living up to Parental Expectation Inventory, Academic Self-Efficacy Scale, and The Utrecht Work Engagement Scale for Students to assess students’ perceived parental expectations, academic self-efficacy, and academic engagement. Quantitative data was analyzed by descriptive statistical technique and referential statistical technique. Results showed that there is a moderate significant positive correlation between student’s perceived parental expectations and academic engagement, and similarly, there is a moderate significant positive correlation between academic self-efficacy and academic engagement. The results of hypothesis testing found that hypothesis on the direct significant effects of students’ perceived parental expectations on academic engagement has been rejected, indicating the mediation effects of academic self-efficacy.